Régimen histórico jurídico catastral, vinculado a la propiedad y pago del impuesto predial - Nizama Valladolid, Medardo (2025)
The present updating study focuses on conducting a critical analysis from historical, legal, economic, and educational perspectives regarding the origins of the cadastre. It examines its relationship with the real estate property registry and its application in the tax system, as well as the compliance with property tax payments in several districts of Lima. Furthermore, it evaluates the influence of these factors on the financing of public works and services, while comparing the cadastral experiences of Colombia and Mexico.The research employs methods of analysis and synthesis, along with techniques such as comprehensive reading, data recording, and documentary compilation. The findings reveal significant conclusions: the absence of a unified and up-to-date cadastre, and the existence of multiple, inconsistent cadastral systems that hinder efficient management and development. It is also demonstrated that the devaluation of properties leads to poor tax collection and distorts the real estate market, while tax evasion negatively impacts municipal financial activity. Finally, the study highlights a widespread lack of knowledge regarding tax obligations and the benefits of an integrated cadastre, coupled with insufficient investment in education, training, and technology factors that limit the modernization and efficiency of cadastral management in both district and provincial municipalities.